Effects of photofunctionalization on early osseointegration of titanium dental implants in the maxillary posterior region: a randomized double-blinded clinical trial - Bada Choi; Ye Chan Lee; Kyung Chul Oh; Jae Hoon Lee (SpringerOpen, 2021)
Abstract Background This study aimed to investigate the effects of ultraviolet (UV) photofunctionalization on the stability of implants during the early phase in the posterior region of the maxilla. The study was a randomized double-blinded clinical trial. Half of the participants received conventional commercial implants while the other half received UV-irradiated implants. The surgical sites were classified into three bone quality groups (II, III, IV) based on the grayscale value measured on cone-beam computed tomography. The values obtained from resonance frequency analysis were recorded immediately after implant placement and at 4 weeks and at 4 months postoperatively. The marginal bone level of the implants was evaluated using periapical radiographs at 4 weeks, 4 months, and 1 year postoperatively. Results Fifty-seven implants placed in 34 participants were analyzed in this study. In group III, significant differences were observed in terms of the differences of resonance frequency analysis values at 4 weeks (p = 0.004) and 4 months (p = 0.017) postoperatively. In group II, the UV-treated group showed significantly lesser bone loss at 4 weeks post-operatively (p = 0.037). Conclusions Within the limitation of the present study, we concluded that UV surface treatment on implants may increase the initial stability in the region of the maxilla with poor bone quality.